2021
DOI: 10.3389/fphy.2021.671997
|View full text |Cite
|
Sign up to set email alerts
|

A Bi-Axial Quantum State That Controls Molecular Collisions Like a Double-Slit Interferometer

Abstract: To control molecular scattering, we consider hydrogen molecules prepared in a coherent superposition of m states within a single rovibrational (v, j) energy eigenstate using Stark-induced adiabatic Raman passage (SARP). Specifically, SARP can prepare a bi-axial state of the HD molecule in which the HD bond axis exists simultaneously in two possible alignments at right angles to one another with a well-defined relative phase. We show that scattering from this biaxial state will interfere, resulting in a φ -depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As such, scattering from the coupled orientations of the biaxial state mimics the way that a photon or particle simultaneously experiences the two mechanical slits in a traditional double-slit scattering experiment. Our earlier theoretical study ( 37 ) showed that the biaxial state is capable of producing an interference pattern in the scattering intensity in the plane perpendicular to the collision velocity. In this study, we experimentally demonstrate the double-slit action and show that the interference is evident in the scattering distribution projected parallel to the collision velocity.…”
mentioning
confidence: 99%
“…As such, scattering from the coupled orientations of the biaxial state mimics the way that a photon or particle simultaneously experiences the two mechanical slits in a traditional double-slit scattering experiment. Our earlier theoretical study ( 37 ) showed that the biaxial state is capable of producing an interference pattern in the scattering intensity in the plane perpendicular to the collision velocity. In this study, we experimentally demonstrate the double-slit action and show that the interference is evident in the scattering distribution projected parallel to the collision velocity.…”
mentioning
confidence: 99%
“…For inelastic collisions of NO­(A 2 Σ) with He, Chandler and co-workers determined how the orientation of the product’s angular momentum ( j ′) depends on the initial orientation of the NO molecule . In Brouard’s group, differences in the differential cross-sections (DCSs) for collisions between rare gases (Rg) and NO­(X 2 Π) molecules were observed depending on the NO orientation: whether the collision was head-on or side-on and whether the Rg hits the molecule close to the O or N atom. Zare and co-workers exploited the combination of copropagating molecular beams with the Stark-induced adiabatic Raman passage (SARP) method for state preparation and alignment of the molecules. , In these experiments, the colliding molecules are copropagated in the same molecular beam, allowing relative collision energies near 1 K although the molecular velocities in the laboratory frame are much higher (about 2000 m/s). This is a particularly interesting regime which, when combined with the SARP method, allows for the study of sterodynamical preferences where only a few partial-waves contribute.…”
mentioning
confidence: 99%
“…Moreover, because the coherent superposition of the degenerate m states is stationary in time, it can be used to coherently control a bimolecular reaction. Some of these controls have already been demonstrated in the cold scattering experiments and also have been discussed theoretically. ,,, …”
Section: Sarp Control Of Internal States and Collision Geometrymentioning
confidence: 92%